¿Qué se esconde detrás del testimonio? La búsqueda de la verdad más allá del discurso - Alday Pumaricra, José Andrés (2025)
This article critically analyzes the limits of the techniques currently used to assess the credibility of testimony in criminal proceedings, questioning the excessive reliance on intuition, nonverbal language, and other pseudoscientific practices lacking empirical support. From a philosophical and legal perspective and through critical documentary analysis of scientific literature, case law, and doctrinal sources, the author examines the epistemic validity of tools such as the polygraph, neuroscience, and the psychology of testimony. The author concludes that none of these techniques reliably detects lies, and that the assessment of testimony should focus on the reliability of the content—not on the subjective credibility of the declarant—with support from verifiable empirical evidence, to avoid judicial errors arising from biases or irrational intuitions.